Synchronous endometrial and ovarian cancer: a rare presentation - Yadav, Reena; Jaiswal, Nishtha; Yadav, Ruby; Kumar, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Synchronous primary cancers are relatively uncommon in the general population. About 0.5 -1.7% of gynecological malignancies have synchronous primary cancer of female genital tract. Amongst the synchronous gynecological malignancies synchronous endometrioid carcinoma is most common and has good prognosis. Patients with synchronous endometrioid tumors of endometrium and ovary are usually younger, have low grade number, and their prognosis is better than other histologic types. The authors are presenting a case of 38 years old nulliparous obese woman with pain in abdomen and heavy menstrual bleeding for a duration of four months. The MRI pelvis was suggestive of well defined, lobulated, complex, solid cystic multiseptated lesion measuring 8.8×7.7×8.8 cm in right adnexa, with anteverted uterus, and a bulky indistinct emdomyometrial junction. Histopathology revealed synchronous endometrial carcinoma of both uterus and ovary.